Avaliação do conhecimento e práticas de prevenção e controle da Covid-19 dos usuários da atenção básica do município de São José dos Campos - Silva, Mariana (2022)
As of June 1, 2021, 16,545,55 cases of COVID-19 were confirmed, with 462,791 deaths in Brazil. The Southeast region concentrated 6,191,324 cases of Covid-19, with 213,245 deaths, being the first region in the country in number of cases. In the municipality of São José dos Campos, 72,576 cases of COVID-19 and 1,496 deaths were confirmed.3,4,5 People's adherence to prevention and control measures is affected by their knowledge, attitudes and practices in relation to COVID-19.6 This field study aims to quantify and evaluate the knowledge of primary care users about Covid-19 prevention and control practices in the municipality of São José dos Campos. To this end, a questionnaire was applied in two ways: electronic, via the Google Forms digital platform, disseminated through a QR Code contained in informative posters posted on the wall/walls of the Basic Health Units and physically, by printed form, which was distributed visits to the units. Upon sending the questionnaire, the participants received a health education strategy, in which they had access to the complete feedback with scientifically justified answers to all questions, enabling the review and correction of knowledge. It is concluded that although some issues have generated contradictions and/or doubts on the part of users of basic health units, they have demonstrated relevant knowledge regarding the Covid-19 disease.